ANALISIS KONTRASTIF KALIMAT SYARAT BAHASA ARAB DAN BAHASA INDONESIA - Qistifani, Vini Qonita (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2019)
This study aims to determine the sentence structure of Arabic and Indonesian terms in Surah Al-Baqarah, their similarities and differences, and their implications for translation. The research method used in this study is a descriptive method with a qualitative approach. Data collection techniques used were documentation and triangulation studies. From the results of this study, researchers found 190 the number of shar'iyah in surah Al-Baqarah with various sentence structures. Then, some similarities and differences in the structure between the sentence terms in Arabic and Indonesian, as well as the implications of this study, the researcher found a tendency to translate adawat syará¹ on the translation of the Ministry of Religion and Al-Mishbah.